Design and Implementation of Intelligent Anti-Interference for Data Link - Zhen WU; Jingyu YANG; Shuo WANG; Zhenghuan WANG; Min JIA (天地一体化信息网络)
The application scenarios and problems faced by data link communication on hypersonic unmanned aerial vehicles were introduced, and the mainstream jamming style categories, development trends and anti-jamming methods in current data link communication were listed.The design and technical scheme of the intelligent anti-jamming engine was described in detail, and the design of the intelligent anti-jamming engine was discussed from four aspects: the overall scheme, the broadband spectrum perception module, the interference signal recognition module, and the anti-interference decision-making module.The technical approaches of the main key technologies were introduced, the performance of the adopted methods was simulated and tested.The results of the simulation tests were compared and analyzed, and the simulation tests could proved that the methods used could achieved the expected goals, but there were still certain limitations, and the actual engineering and practical eff ects need to be further verifi ed.